Análise paleográfica de manuscritos do acervo do Instituto de Terras do Pará - ANDRADE, Ely Anne Monteiro (2022)
This paper presents a paleographic analysis of manuscript documents from the permanent collection of the Instituto de Terras do Pará (ITERPA). The choice of this theme emerged from classroom readings in the context of the Paleography discipline and a technical visit to the archive of the Instituyo de Terras do Pará (ITERPA), within the scope of the History of Brazil and Collection Formation discipline. Reading, transcription, identification and analysis of the graphic aspects of the manuscripts were performed. From the methodological perspective, the work had an exploratory character, having been carried out bibliographical, documentary and field research. The bibliographic and documentary research provided deepening on the subject of the study, as base the main authors that talk about the paleography, the writing, the permanent archive and manuscript. The field research was carried out from the visit to the physical file of ITERPA, which in view of the contact with various land tenure registration processes, were selected two documents for the application of the proposed objectives. It concludes by reaffirming the importance of palaeography for accessing and understanding information from document contents